Alfabetização digital na biblioteca pública : fortalecendo sua função social para mitigar a exclusão digital - Moura, Mariana Silva (Universidade Federal de São Carlos, 2024)
The research investigates the role of public libraries in promoting Digital Literacy to address digital exclusion, emphasizing their social responsibility and alignment with the UN Sustainable Development Goals (SDGs). The objective is to evaluate the implementation of theoretical guidelines and the global consistency of progress in Digital Literacy. Using a multi-method approach, the research includes a qualitative and bibliographic dimension with a systematic review; and an exploratory dimension with the investigation of Digital Literacy initiatives in libraries worldwide. It also adopts a quantitative perspective when developing bibliometric indicators to analyze scientific production, aiming for a comprehensive and multifaceted understanding of the current state of Digital Literacy in the library context. The systematic review of 43 scientific articles reveals challenges such as the lack of training of information professionals and the need for adequate investment in public libraries. Still, it highlights the crucial role of these institutions in promoting digital inclusion. The studies analyzed address the future of digital literacy and the application of theoretical frameworks to deal with emerging social issues, such as exclusion from the digital labor market and digital inequality. In developed countries, there is a notable increase in studies on digital learning among elderly and middle-aged adults. In countries with public investment difficulties, actions focus on community practices. Various forms of digital literacy are identified, reflecting a growing concern about the digital exclusion of marginalized groups. Practical activities in world-leading libraries include workshops on device use, guidance on configuration and use of tools, web security workshops, work tools courses, and digital inclusion programs for different demographic groups. In general, the programs identified are aimed at basic computing, with a special focus on continuing education, digital security, awareness, inclusion, accessibility, and a concern for the future of work. The actions show a significant intersection between literature and practice, proving a commitment to digital inclusion and accessibility, especially in contexts marked by technological obstacles and informational vulnerabilities. Three factors are identified: digital literacy is more common in well-funded libraries; most activities focus on basic digital skills, but there is a demand for more advanced programs; and nations’ digital plans are advancing, driven by economic motivations. It is concluded that, although there are efforts to reduce the digital divide by promoting basic digital skills, it is essential to expand access to advanced digital literacy to address complex issues such as critical thinking about technology and the impact of artificial intelligence. Such a measure is crucial to prevent less developed countries from facing a scenario of digital illiteracy, which could lead to a significant increase in underemployment or even absolute unemployment. Moving beyond training for the job market, exploring digital citizenship and social evolution in a world influenced by artificial intelligence, is essential.

La investigación investiga el papel de las bibliotecas públicas en la promoción de la alfabetización digital para abordar la exclusión digital, enfatizando su responsabilidad social y su alineación con los Objetivos de Desarrollo Sostenible (ODS) de la ONU. El objetivo es evaluar la implementación de lineamientos teóricos y la consistencia global del progreso en Alfabetización Digital. Utilizando un enfoque multimétodo, la investigación incluye una dimensión cualitativa y bibliográfica con una revisión sistemática; y una dimensión exploratoria con la investigación de iniciativas de Alfabetización Digital en bibliotecas de todo el mundo. También adopta una perspectiva cuantitativa al desarrollar indicadores bibliométricos para analizar la producción científica, buscando una comprensión integral y multifacética del estado actual de la Alfabetización Digital en el contexto bibliotecario. La revisión sistemática de 43 artículos científicos revela desafíos como la falta de formación de los profesionales de la información y la necesidad de una inversión adecuada en las bibliotecas públicas, pero destaca el papel crucial de estas instituciones en la promoción de la inclusión digital. Los estudios analizados abordan el futuro de la alfabetización digital y la aplicación de marcos teóricos para abordar cuestiones sociales emergentes, como la exclusión del mercado laboral digital y la desigualdad digital. En los países desarrollados, hay un aumento notable de estudios sobre el aprendizaje digital entre adultos mayores y de mediana edad. En países con dificultades de inversión pública, las acciones se centran en prácticas comunitarias. Se identifican varias formas de alfabetización digital, lo que refleja una creciente preocupación por la exclusión digital de los grupos marginados. Las actividades prácticas en bibliotecas líderes a nivel mundial incluyen talleres sobre uso de dispositivos, orientación sobre configuración y uso de herramientas, talleres de seguridad web, cursos de herramientas de trabajo y programas de inclusión digital para diferentes grupos demográficos. En general, los programas identificados están dirigidos a la informática básica, con especial foco en la educación continua, la seguridad y concienciación digital, la inclusión y accesibilidad, y la preocupación por el futuro del trabajo. Las acciones muestran una intersección significativa entre la literatura y la práctica, demostrando un compromiso con la inclusión y la accesibilidad digitales, especialmente en contextos marcados por obstáculos tecnológicos y vulnerabilidades informativas. Se identifican tres factores: la alfabetización digital es más común en bibliotecas bien financiadas; la mayoría de las actividades se centran en habilidades digitales básicas, pero existe una demanda de programas más avanzados; y los planes digitales de las naciones avanzan, impulsados ​​por motivaciones económicas. Se concluye que, si bien existen esfuerzos para reducir la brecha digital mediante la promoción de habilidades digitales básicas, es fundamental ampliar el acceso a la alfabetización digital avanzada para abordar cuestiones complejas como el pensamiento crítico sobre la tecnología y el impacto de la inteligencia artificial. Una medida de este tipo es crucial para evitar que los países menos desarrollados enfrenten un escenario de analfabetismo digital, que podría conducir a un aumento significativo del subempleo o incluso del desempleo absoluto. Es fundamental ir más allá de la formación para el mercado laboral y explorar la ciudadanía digital y la evolución social en un mundo influenciado por la inteligencia artificial.
Digital literacy in the public library: strengthening its social function to mitigate digital exclusion
Alfabetización digital en la biblioteca pública: fortaleciendo su función social para mitigar la exclusión digital
Keywords: Alfabetização digital; Exclusão digital; Biblioteca pública; Alfabetização midiática e informacional; Agenda 2030; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA